Influence of irrigation on the Sunn pest Eurygaster integriceps Put. (Insecta: Heteroptera) in the Central Forest-Steppe of Ukraine - Melnichuk, Fedir; Alekseeva, Svitlana; Hordiienko, Oleksandra; Nychyporuk, Oleksii; Borysenko, Andrii (Ecological Questions, 2023)
The aim of the research is to establish the influence of watering on the phenological and biological features of winter wheat pests development, in particular Sunn pests. Trials were conducted on winter wheat crops under sprinkler irrigation in 2015-2020 in conditions of the Central Forest-Steppe of Ukraine. The size of the experimental plots in the field experiments was 50 m2 (10.4x4.8 m) at the 4 times replication. The allocation of plots was randomized. The average numbers of Sunn pest nymphs in 2015-2020 were 0.7-2.7 exemplars/m² on non-irrigated winter wheat crops and 0.8-3.8 exemplars/m² on irrigated. The share of the factor “presence of irrigation” that impacts on the number of Sunn pests reaches 80.2%. The sums of degree-days necessary for the beginning of different development stages of this phytophagous were calculated. The stage of the revival of Sunn pest nymphs began in mid-May – the first decade of June, which coincided with the phases of development of winter wheat: the end of flowering – soft dough ripening of the grain. The sum of degree-days required for the beginning of this stage was 177.8-233.8°C without irrigation, while in sprinkler irrigation conditions – 275.5-349.1°C. For the beginning of the transformation of the fifth instar nymphs into adults, the required sum of degree-days was 410.5-481.5°C on the non-irrigated crops and 545.7-630.4°C – under conditions of irrigation. Clarifying the sum of degree-days required for different stages of Sunn pest development will allow for predicting the terms of protective measures against this pest in the field conditions under irrigation.